Meningkatkan Keterampilan Berbicara Peserta Didik Sekolah Dasar Melalui Pendekatan Komunikatif - Aripi Aripi; Rohani Rohani (Jurnal Didaktika Pendidikan Dasar, 2023)
The purpose of this study was to determine the extent to which the communicative approach was able to give the right influence the speaking skills of elementary school students. The method used in this study was action research. This research was conducted at SD Negeri Bile Tengak, the research subjects were 24 students of class V-A consisting of 11 male students and 13 female students. The participants involved in this research are the researchers themselves who act as teachers who teach in class V-A and class V-B teachers as collaborators. The instrument used in this study is an observation sheet. There is a significant difference in speaking skills through a communicative approach in fifth-grade students with the theme “Objects in the Surrounding Environment,” sub-theme “Humans and the Environment”. In the first cycle, 13 students (54.17%) completed it, and 11 students (45.83%) had not completed it. Meanwhile, in the second cycle of the second theme "Events in Life", the sub-theme "Various Events in Life", 18 students (75%) completed it, and 6 students (25%) did not complete it with an average score of 80.